ANALYSIS OF ELEMENT ‘UNLAWFUL’ OF CORRUPTION IN THE BANKING SECTOR (STUDY OF THE SUPREME COURT DECISION NUMBER 1812 K / PID.SUS / 2014) - Angga Wijaya Holman Fasa; Ferianto Ferianto; Tommy Hendrix (Jurnal Hukum dan Peradilan, 2020)
The banking sector as one of the drivers of the national economy plays an important role in funding a business through bank credit distributing activities. In practice, this banking service raises legal problems, not only banking crimes but also corruption. Supreme Court Decision No. 1812 K / PID.SUS / 2014 on behalf of the Defendant Dian Siswanto, S.E. MM., in the case of a corruption shows this. This paper examines the element of unlawful and abuse of authority in cases of corruption in the banking sector. The research method used is normative law which is prescriptive with a statute approach, a conceptual approach, and a case approach. The results show 2 (two) things, first, that the defendant's actions met the unlawful element in the act of corruption as charged in the primary indictment. Second, the judge had wrongly in the application of law based on the subsidiary indictment concerning abuse of authority which was not fulfilled. The judge in this case, was not punctilious in digging up legal facts and was not correct in applying the law. Therefore, in the case of deciding a case, if the charges are of subsidiarity, the judge should prove the primary indictment carefully before deciding based on the subsidiary indictment to create justice, benefit and legal certainty in law enforcement in general, and especially for the accused.